2017
DOI: 10.3788/col201715.051603
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced spatial terahertz modulation based on graphene metamaterial

Abstract: The plasmonic mode in graphene metamaterial provides a new approach to manipulate terahertz (THz) waves. Graphene-based split ring resonator (SRR) metamaterial is proposed with the capacity for modulating transmitted THz waves under normal and oblique incidence. Here, we theoretically demonstrate that the resonant strength of the dipolar mode can be significantly enhanced by enlarging the arm-width of the SRR and by stacking graphene layers. The principal mechanism of light-matter interaction in graphene metam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Its conduction band and valence band meet at the Dirac point. Accordingly, graphene is equivalent to a zero-gap semiconductor with electron mobility exceeding 15,000 cm 2 • V −1 • s −1 at room temperature [1] , which endows graphene excellent electrical and optical properties and prompts a wide range of potential applications in the perfect absorption of optoelectronic devices, optical communication systems, as well as sensing devices [2][3][4][5][6][7][8] . Due to monolayer graphene itself being incapable of exciting surface plasmon resonances, its theoretical absorption efficiency in air is exclusively about 2.3% of the single-pass light [9] , which seriously obstructs its application range and device performance.…”
Section: Introductionmentioning
confidence: 99%
“…Its conduction band and valence band meet at the Dirac point. Accordingly, graphene is equivalent to a zero-gap semiconductor with electron mobility exceeding 15,000 cm 2 • V −1 • s −1 at room temperature [1] , which endows graphene excellent electrical and optical properties and prompts a wide range of potential applications in the perfect absorption of optoelectronic devices, optical communication systems, as well as sensing devices [2][3][4][5][6][7][8] . Due to monolayer graphene itself being incapable of exciting surface plasmon resonances, its theoretical absorption efficiency in air is exclusively about 2.3% of the single-pass light [9] , which seriously obstructs its application range and device performance.…”
Section: Introductionmentioning
confidence: 99%
“…Metamaterial absorbers showcase huge application value in communication, security, detection and other fields, and have increasingly become one of the study hotspots in terahertz region [11][12][13][14][15][16][17][18][19][20]. Landy et al reported a metamaterial absorber with perfect absorption characteristics for the first time [21].…”
Section: Introductionmentioning
confidence: 99%